Control of vortex shedding from a circular cylinder surrounded by eight rotating wake-control cylinders at Re=100. (August 2019) - Assi, G.R.S.; Orselli, R.M.; Silva-Ortega, M.
Abstract: The present work investigates the suppression of vortex shedding of a circular cylinder of diameter D surrounded by a polar array 8 rotating wake-control cylinders of a considerably smaller diameter d ∕ D = 0 . 05 . A numerical approach was employed to simulate the laminar flow at a Reynolds number of 100. The governing equations were discretised by the finite volume method for a two-dimensional computational domain. The main varying parameter was the rotation speed of the control cylinders, measured as a fraction of the incoming flow speed. A controlled wake (one without alternating vortices) was achieved when the tangential velocity at the surface of the control cylinders was greater than 3 times the free stream velocity. A significant reduction of the overall drag coefficient and mitigation of the unsteady hydrodynamic forces acting on the system were observed as rotation was increased. Given enough rotation, a negative mean drag (thrust) was achieved. The power spent to rotate the 8 control cylinders appeared to be higher than the power-loss associated with the mean drag of a bare cylinder. While still working with an active, open-loop control system, this investigation supports the development of a closed-loop wake-control device for offshore applications.